Investigating online gender empowerment campaigns: a multimodal feminist discourse analysis approach - Yasmeen Ezzat Elgreatly; Inas Hussein Hassan; Riham Abdelmaksoud Debian (Insights into Language, Culture and Communication, 2024)
Women's empowerment and the promotion of women's rights have emerged as significant global movements, continually breaking new ground. This thesis aims at investigating how women empowerment is visually and verbally codified in advertisements. This study examines two beauty advertisement campaigns launched by Olay and Reebok in 2018: Olay's "#FaceAnything" campaign and Reebok's "#BeMoreHuman" campaign. Both campaigns aim to empower women to believe in themselves. These campaigns focus on promoting awareness of women's individuality rather than asserting women's superiority over men. Presented in the form of advertisements, these campaigns use discourse crafted by producers to convey persuasive messages. To unveil the empowering messages in these advertisement campaigns, this study employs Multimodal Theory of Visual Grammar by Kress and van Leeuwen (2006) and Michelle M. Lazar’s Feminist Critical Discourse Analysis (2005; 2007) framework. The findings reveal that both campaigns utilize a variety of linguistic and visual techniques to empower women, challenge traditional gender roles, and promote feminist values. Furthermore, this study explores the inversion of patriarchal discourse within these campaigns as a strategy to empower women. By subverting traditional gender roles and expectations, both Olay and Reebok campaigns challenge patriarchal norms and assert feminist identity and positionality. This analysis sheds light on how advertising language is utilized as a powerful tool to empower women, promote gender equality, and contribute to the ongoing conversation about gender representation in advertising. Keywords:  women empowerment, advertisements, Feminist Critical Discourse Analysis, Visual Grammar Received: 23 September 2024 Accepted: 06 November 2024 Published: 24 November 2024